Perencanaan Pembangunan : The Impact of Decentralization on Urban Development: Case Study of Indonesia - Grahayudiandono, Prakoso (Kementerian PPN/Bappenas, 2016)
Since implementing the decentralization mechanism back in 2001, Indonesia's regional province/district/cities have been mushroomed. Having rapid changes in its administrative system has brought many implications on how the urban development poolicy shapes the change of the livelihood. Some of the scholars argue that decentralization process would bring negative aspects.